AUTHORING, PEDAGOGY AND THE WEB: EXPECTATIONS VERSUS REALITY - Bangs, Paul (International Journal of English Studies, 2002)
The Internet has stimulated enormous expectation in many fields of learning, including language acquisitiori. From a position in which technology enhanccd language learning was at the forefront of pedagogic development, we now see a situation in which good design - both pedagogic and instructional - is all too often sacrificed for the sake of technological convenience. Some of the techniques which were possible using multimedia on a CD-ROM platform have all but disappeased as end users expect to find good learning experiences from the Web. One major reason why good design principles are often ignored in web-based learning design is the lack insuficient. easy-to-use authoring tools, leading to an over-reliance on simple Iiypcstext routines (though even with tliese there is no excuse for the woeful neglect of feedback techniques so ol’ten encouiiiered). or the need to rely on technically trained personnel with an insuficiciit understanding of clear instructional design principles. I Iclp is bEginning to arrive with sonlc good authoring systems, and this work looks at Hot Potatoes and MALTEB, whilst at the same time postulating that a clear approach to pedagogic issues and. above all. instructional design work, cari still create sound learning programs with even simple hypertext tools. l’he work concludes with a practical check-list of advice for the would-be author o l language learning programs.